(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article, the authors examined the types of evidence, the basis of the classification of evidence, the practical importance of the classification of evidence, and analyzed the opinions of various authors regarding the classification of evidence. Key words: evidence, classification, sources of evidence, alibi.